ANALYSIS THE INFLUENCE OF REGIONAL FINANCIAL MANAGEMENT ELEMENTS ON PERFORMANCE OF DISTRICT / CITY SKPD AND ITS IMPLICATIONS ON PUBLIC SERVICES IN PROVINCE OF NORTH MALUKU (International Conference of Graduate School on Sustainability (ICGSS), 2018)
This study aims to describe the elements of the local financial management that include: the effectiveness of financial planning, the effectiveness of budget execution, control, transparency and accountability of financial reporting, the effectiveness of internal and external party supervision, and the performance of the Regional Device Work Unit, as well as the public service; analyze the influence of effectiveness of financial planning, effectiveness of budget execution, control, transparency and accountability of financial reporting, and internal and external effectiveness of party supervision on the performance of Local Government Work Unit; analyze the influence of effectiveness of financial planning, effectiveness of budget execution, control, transparency and accountability of financial reporting, and effectiveness of internal and external party supervision on public services; analyze the effect of the performance of the Local Government Work Unit on public services; and analyze the influence of effectiveness of financial planning, effectiveness of budget execution, control, transparency and accountability of financial reporting, and the effectiveness of internal and external party supervision on public service through the performance of Local Government Work Unit. The analysis technique used is descriptive analysis and structural equation modeling analysis.The effectiveness of financial planning, the effectiveness of budget execution, control, transparency and accountability of financial reporting, and the effectiveness of internal and external supervision of party have an effect on the performance of Local Government Work Unit. The effectiveness of financial planning, the effectiveness of budget execution, control, transparency and accountability of financial reporting, and the effectiveness of internal and external oversight of supervisors on public services. The performance of the Local Government Work Unit influences public services. The effectiveness of financial planning, the effectiveness of budget execution, control, transparency and accountability of financial reporting, and the effectiveness of internal and external party Affect supervision of public services through the performance of Local Government Work Units. The performance of the Local Government Work Unit influences public services. The effectiveness of financial planning, the effectiveness of budget execution, control, transparency and accountability of financial reporting, and the effectiveness of internal and external party Affect supervision of public services through the performance of Local Government Work Units. The performance of the Local Government Work Unit influences public services. The effectiveness of financial planning, the effectiveness of budget execution, control, transparency and accountability of financial reporting, and the effectiveness of internal and external party Affect supervision of public services through the performance of Local Government Work Units.